Pengaruh Workload Terhadap Kinerja Pegawai Dengan Stres Kerja Sebagai Variabel Intervening Pada Pegawai RSUD H. A. Sulthan Daeng Raja Kabupaten Bulukumba Di Masa Pandemi-19 - Jusmiati, Asrini; Akhmad jafar, Akhmad jafar; Suhartini, Eka (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
ABSTRACT The objectives of this study are: 1) To determine the effect of workload on employee performance. 2) To determine the effect of workload on work stress. 3) To determine the effect of work stress on performance. 4) To determine the effect of workload on performance through work stress as an intervening variable. This research is a quantitative research type and the research sample is 177 employees of RSUD H. Andi Sulthan Daeng Radja, Bulukumba Regency. This study uses path analysis for data analysis with the help of SPSS Version 26 Statistics program. The results of this study prove that: 1) Workload has a positive and significant effect on performance. 2) Workload has a positive and insignificant effect on work stress. 3) Job stress has a negative and significant effect on performance. 4) Job Stress does not mediate Workload on Performance. Keywords: Workload, Job stress, Performance